The ability of banks to lend to informationally opaque small businesses - Berger, Allen N.; Klapper, Leora F.; Udell, Gregory F. (Journal of Banking & Finance, 2001)
We test hypotheses about the effects of bank size, foreign ownership, and distress on lending to informationally opaque small firms using a rich new data set on Argentinean banks, firms, and loans. We also test hypotheses about borrowing from a single bank versus multiple banks. Our results suggest that large and foreign-owned institutions may have difficulty extending relationship loans to opaque small firms. Bank distress appears to have no greater effect on small borrowers than on large borrowers, although even small firms may react to bank distress by borrowing from multiple banks, raising borrowing costs and destroying some relationship benefits.